Trunk Muscle Activity during Drop Jump Performance in Adolescent Athletes with Back Pain - Mueller, Steffen; Stoll, Josefine; Mueller, Juliane; Cassel, Michael; Mayer, Frank (Frontiers in Physiology, 2017)
In the context of back pain, great emphasis has been placed on the importance of trunk stability, especially in situations requiring compensation of repetitive, intense loading induced during high-performance activities, e.g. jumping or landing. This study aims to evaluate trunk muscle activity during drop jump in adolescent athletes with back pain (BP) compared to athletes without back pain (NBP). Eleven adolescent athletes suffering back pain (BP: m/f: n=4/7; 15.9±1.3y; 176±11cm; 68±11kg; 12.4±10.5h/we training) and 11 matched athletes without back pain (NBP: m/f: n=4/7; 15.5±1.3y; 174±7cm; 67±8kg; 14.9±9.5h/we training) were evaluated. Subjects conducted 3 drop jumps onto a force plate (ground reaction force). Bilateral 12-lead SEMG (surface Electromyography) was applied to assess trunk muscle activity. Ground contact time [ms], maximum vertical jump force [N], jump time [ms] and the jump performance index [m/s] were calculated for drop jumps. SEMG amplitudes (RMS: root mean square [%]) for all 12 single muscles were normalized to MIVC (maximum isometric voluntary contraction) and analyzed in 4 time windows (100ms pre- and 200ms post-initial ground contact, 100ms pre- and 200ms post-landing) as outcome variables. In addition, muscles were grouped and analyzed in ventral and dorsal muscles, as well as straight and transverse trunk muscles. Drop jump ground reaction force variables did not differ between NBP and BP (p>0.05). Mm obliquus externus and internus abdominis presented higher SEMG amplitudes (1.3-1.9-fold) for BP (p<0.05). Mm rectus abdominis, erector spinae thoracic/lumbar and latissimus dorsi did not differ (p>0.05). The muscle group analysis over the whole jumping cycle showed statistically significantly higher SEMG amplitudes for BP in the ventral (p=0.031) and transverse muscles (p=0.020) compared to NBP. Higher activity of transverse, but not straight, trunk muscles might indicate a specific compensation strategy to support trunk stability in athletes with back pain during drop jumps. Therefore, exercises favoring the transverse trunk muscles could be recommended for back pain treatment.